ANALISIS PENGARUH SURFACE ROUGHNESS, TEMPERATUR SUBSTRAT, DAN JENIS MATERIAL ABRASIVE TERHADAP BIAYA PROSES MENGGUNAKAN METODE TAGUCHI - Rachman, Farizi; Mutiara, Arun Sukma; Indrawan, Rizal; Setiawan, Tri Andi; Bisono, Fipka; Purnomo, Dhika Aditya; Hamzah, Fais (AUSTENIT, 2024)
The wrapping up and portray fabricating handle may be a organize of venture work at PT. Lintech Duta Pratama. Disgraceful portray forms result in absconds. Items that have absconds require repair so they can at that point be sent to clients. Rehashed repair forms cause expanded handle costs and obstruct item conveyance. In this manner, to get great item quality and diminish handle costs, inquire about to obtain ideal parameter settings is required. The method parameters considered are surface harshness, substrate temperature, and sort of abrasive fabric. The experimental design used is the taguchi method in the form of an orthogonal matrix . From the exploratory comes about, the ideal combination of handle parameters for prepare costs was gotten, to be specific surface harshness at level 1 with a esteem of 50 Î¼m, temperature at level 2 with a esteem of 34 Â° C, and rough fabric sort at level 2 with steel coarseness.